2013
DOI: 10.1111/iju.12266
|View full text |Cite
|
Sign up to set email alerts
|

Regenerative treatment of male stress urinary incontinence by periurethral injection of autologous adipose‐derived regenerative cells: 1‐year outcomes in 11 patients

Abstract: Abbreviations & AcronymsObjectives: To assess the efficacy and safety of a novel cell therapy for male stress urinary incontinence consisting of periurethral injection of autologous adipose-derived regenerative cells, and to determine the 1-year outcomes. Methods: A total of 11 male patients with persistent stress urinary incontinence after prostate surgery were included in the study. The Celution system was used to isolate adipose-derived regenerative cells from abdominal adipose tissue obtained by liposuctio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
99
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 90 publications
(102 citation statements)
references
References 22 publications
3
99
0
Order By: Relevance
“…These were essentially preclinical studies that used isolated muscle progenitor cells or ex vivo cultured MSCs from bone marrow (12), fat (13)(14)(15)(16) or cord blood (17). Four Phase I clinical studies have reported the efficacy of MSC in SUI, (18) in the context of a post-prostatectomy (19) feminine SUI after the failure of a first line pelvi-perineal physiotherapy or surgical treatment (20,21). The appearance of clinical efficacy and a delayed increase in MUP between 3 and 6 months after the injection of MSC were in favour of a simple bulking effect (5).…”
Section: Results Of Svf Injectionsmentioning
confidence: 99%
“…These were essentially preclinical studies that used isolated muscle progenitor cells or ex vivo cultured MSCs from bone marrow (12), fat (13)(14)(15)(16) or cord blood (17). Four Phase I clinical studies have reported the efficacy of MSC in SUI, (18) in the context of a post-prostatectomy (19) feminine SUI after the failure of a first line pelvi-perineal physiotherapy or surgical treatment (20,21). The appearance of clinical efficacy and a delayed increase in MUP between 3 and 6 months after the injection of MSC were in favour of a simple bulking effect (5).…”
Section: Results Of Svf Injectionsmentioning
confidence: 99%
“…At present, the target diseases of treatment with ADSCs are wide-ranging, including fistulas, ischemic heart disease, peripheral artery disease, inflammatory bowel disease, urinary incontinence, and plastic reconstructive surgery [31][32][33][34][35][36]. Cultured or passaged ADSCs are used to treat some of these diseases [31,32,35]; in other cases, purified ADSCs with noncultured or passaged SVF are administered, as in this study, which used a Celution system [33,34,36]. The results of phase II and III studies of complex anal fistulas, pathologically similar to the enterocutaneous fistulas examined in this study, treated with cultured ADSCs have already been reported [31,32].…”
Section: Discussionmentioning
confidence: 99%
“…Secondly, harvesting procedure of ASC is less complicated and is associated with less morbidity and complications. Several recent studies indicate potential clinical use of ASC in BTE (Zuk et al 2001 ;Sándor et al 2013 ;Gotoh et al 2014 ). Despite the above advantages, both in vitro and in vivo osteogenic ability of ASC seem to be inferior as compared to that of BMSC (Liao and Chen 2014 ).…”
Section: Oral Stem Cells In Regenerative Dentistrymentioning
confidence: 99%